Foreign-body granuloma around hair fragments in giant speckled lentiginous nevus: a differential diagnosis of melanoma. - Ingravallo, G.; Lospalluti, M. (European Journal of Pediatric Dermatology, 2023)
Speckled lentiginous nevus is a congenital freckled nevus on which melanocytic nevi arise more frequently than on healthy skin. Its borders with respect to congenital melanocytic nevus are not always clear-cut and the possible onset of melanoma is a dreaded complication in both disorders. This complication should be suspected in the presence of a swelling that arises in the context of a congenital malanocytic nevus and its removal, which seeks to clarify its nature, is mandatory. Since congenital melanocytic nevi are often associated with hypertrichosis, it can happen that around a pilosebaceous follicle inflammatory granulomas, which can simulate a melanoma, are formed with various types of mechanisms. The current work describes the case of a granuloma formed around hair fragments in a giant speckled lentiginous nevus in a 13-year-old boy.